Material and digital reconstruction of fragmentary dead sea scrolls: the case of 4Q418a - Ben-Dov, Yonatan (Studies on the texts of the desert of Judah, 2022)
Methodology -- 1 Collecting the Materials -- 2 Margin of Error -- 3 Image Manipulation -- 4 Scaling the Images -- 5 Removing the Background -- 6 Finding Information on the Verso -- 7 Finding Wads -- 8 Reading and Text Reconstruction -- 9 Recreating Single Columns Based on Fragments and Parallels -- 10 Font -- Appendix 1: Experiment for Validating the Use of a Custom-Made Font, Eshbal Ratzon, Einat Tamir, and Rivkah Madmoni -- Appendix 2: Automated Font Generation, Bronson Brown deVost -- 11 Damage Patterns -- 12 Placing the Fragments on the Canvas Using the Stegemann Method -- Appendix 3: Margin of Error for Placing the Fragments on the Canvas -- 13 Using One Prepared Copy as a Skeleton for a Second Copy -- Appendix 4: Margin of Error for Chapter 13 -- 14 Introduction to the Material Study of Instruction (Musar LaMevin) --15 Re-Edition of 4Q418a --16 Material and Digital Reconstruction of 4Q418a --17 Conclusion: Movement Towards a Comprehensive Reconstruction of Instruction -- Bibliography -- Index of Scrolls.